Pengaruh Penggunaan Media Film Dokumenter Terhadap Kemampuan Menulis Rangkuman Teks Biografi Siswa Kelas X SMA Swasta Methodist 7 Medan - Diva Karen Gultom; Elly Prihasti Wuriyani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This research aims to determine the ability to write biographical texts of class The method used in this thesis is an experimental method with a One Group design. The population in this study was 25 students in class X of the Medan 7 Methodist Private High School. The data analysis technique used in this research is quantitative data using analysis requirements tests, homogeneity tests and hypothesis tests. The results of the research show that the average score for skills in writing biographical texts before applying the treatment is 61.2, which is classified as poor and does not meet the Minimum Completeness Criteria (KKM), namely 75, while the average score for skills in writing biographical texts while applying the treatment is 81, which is classified as in the good category and has met the Minimum Completeness Criteria (KKM). Based on the t test, the significance level value α=0.05 is obtained with dk = N-1=25-1= 24, so the ttable value is 2.040. Thus it is concluded that tcount > ttable, namely 0.106 > 0.173 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant influence of the use of Documentary Film learning media on the descriptive text writing skills of class